Analisis Kualitas Air Pada Mata Air di Kecamatan Kota Soe Kabupaten Timur Tengah Selatan - Hisreidi Funome; Anna Apriani Maniuk Solo (Magnetic: Research Journal of Physics and It’s Application, 2026)
The increasing urbanization, natural activities, anthropogenic activities, and tourism in springs in Kota Soe District can potentially lead to the entry of contaminants that can decrease water quality. Therefore, monitoring water quality in springs is currently crucial to ensure the sustainability of water resources. This study aims to determine the concentration of physical and chemical parameters and water quality in the Oebesa, Oebesi, and Oenasi springs in Kota Soe District. Water quality was determined by measured physical and chemical parameters, compared the measurement results with water quality standards, and analysis using the water pollution index method. The research indicate that the temperature, pH, TDS, TSS, and BOD at the three springs meet the Class I water quality standards stipulated by Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management for the Water Category. However, the Dissolved Oxygen (DO) values ??of the three springs are relatively low (<6 mg/L) and do not meet these established standards. The pollution index values ??for the Oebesa, Oebesi, and Oenasi springs were 0.456, 0.530, and 0.537, which indicated that the three springs are categorized as being in good condition. This study show that the springs in Kota Soe District remain suitable for use as water sources, however management efforts are required to improved Dissolved Oxygen concentrations.